Dissynergies of mergers among local banks - Thomas Bloch (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2008)
In this paper, we investigate how bank mergers affect bank revenues and present empirical evidence that mergers among banks have a substantial and persistent negative impact on merging banks' revenues. We refer to merger related negative effects on banks' revenues as dissynergies and suggest that they are a result of organizational diseconomies, the loss of customers and the temporary distraction of management from day-to-day operations by effecting the merger. For our analyses we draw on a proprietary data set with detailed financials of all 457 regional savings banks in Germany, which have been involved in 212 mergers between 1994 and 2006. We find that the negative impact of a merger on net operating revenues amounts to 3% of pro-forma consolidated banks' operating profits and persists not only for the year of the merger but for up to four years post-merger. Only thereafter mergers exhibit a significantly superior performance compared to their respective pre-merger performance or the performance of their non-merging peers. The magnitude and persistence of merger related revenue dissynergies highlight their economic relevance. Previous research on post-merger performance mainly focuses on the effects from mergers on banks' (cost) efficiency and profitability but fails to provide clear and consistent results. We are the first, to our knowledge, to examine the post-merger performance of banks' net operating revenues and to empirically verify significant negative implications of mergers for banks' net operating revenues. We propose that our finding of negative merger related effects on banks' operating revenues is the reason why previous research fails to show merger related gains.
Keywords: G34; G21; L25; C23; 330; Mergers and acquisitions; post-merger performance; bank mergers; Sparkasse; Übernahme; Fusion; Unternehmensentwicklung; Synergie; Deutschland